2020
DOI: 10.1108/mip-03-2020-0106
|View full text |Cite
|
Sign up to set email alerts
|

Sport nostalgia builds customer equity and future behavior

Abstract: PurposeThe purpose of this study was to examine the relationships among nostalgia, customer equity and behavioral intentions. Specifically, consumers' intentions of purchase and word of mouth were assessed in this study.Design/methodology/approachA total of 272 responses were collected from football fans in Singapore. This study conducted partial least squares structural equation modeling (PLS-SEM) to test hypotheses using SmartPLS 3.0.FindingsResults showed that the paths from nostalgia to value equity, brand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…Participants of this study showed salience in all five volunteer nostalgia factors, while only volunteer experience and volunteer personal identity meaningfully translated into volunteer intention. In a broader sense, the positive connections between the two volunteer nostalgia factors and volunteer intention resonate well with previous findings that identified nostalgia as a significant antecedent of behavioral responses (Chen et al, 2014 ; Cho, 2020 ; Cho & Chiu, 2021 ; Cho et al, 2021a ; Kessous et al, 2015 ; Kim et al, 2019 ; Leong et al, 2015 ). Especially, in the context of volunteering, Green et al ( 2021 ) found that university students’ nostalgia regarding their university experience positively influenced their intention to volunteer for their alma mater.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Participants of this study showed salience in all five volunteer nostalgia factors, while only volunteer experience and volunteer personal identity meaningfully translated into volunteer intention. In a broader sense, the positive connections between the two volunteer nostalgia factors and volunteer intention resonate well with previous findings that identified nostalgia as a significant antecedent of behavioral responses (Chen et al, 2014 ; Cho, 2020 ; Cho & Chiu, 2021 ; Cho et al, 2021a ; Kessous et al, 2015 ; Kim et al, 2019 ; Leong et al, 2015 ). Especially, in the context of volunteering, Green et al ( 2021 ) found that university students’ nostalgia regarding their university experience positively influenced their intention to volunteer for their alma mater.…”
Section: Discussionsupporting
confidence: 88%
“…Individuals’ nostalgic feelings, or longing for the past (Davis, 1979 ), can emanate from their past experiences (i.e., phenomena) and memories (i.e., remembrance or recalling of the experiences) (Cho et al, 2014 , 2021b ; Fairley & Gammon, 2005 ; Sedikides et al, 2004 ; Wilson, 2005 ). It is a universal and powerful clue to behaviors, since almost everyone, if not all, holds nostalgia (Cho et al, 2014 ), and individuals often act to satisfy their nostalgic desires (Cho & Chiu, 2021 ). In addition, given that past experiences are essential to developing nostalgia (Cho et al, 2019a ) and older individuals are likely to have more past experiences than the young (Goulding, 2001 ; Merchant & Ford, 2008 ; Toledo & Lopes, 2016 ), age can be instrumental to understanding nostalgia as well.…”
Section: Introductionmentioning
confidence: 99%
“…Nostalgia can also induce negative feelings as individuals realize that they cannot have an identical experience again. Nevertheless, as long as the positive feelings far exceed the negative emotions, an individual can still experience nostalgia (Cho and Chiu, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Revisit intention is a derivative of behavioral intention, which is a strong predictor of behavior as highlighted in the theory of planned behavior (Ajzen, 1991). The intention to revisit is widely studied by scholarsparticularly those specializing in the field of tourism, leisure and recreationas intention generally predicts actual behavior and is directly linked to the competitiveness of a certain setting (Cho and Chiu, 2021and Cho et al, 2019d, 2020a. According to Baker and Crompton (2000), revisit intention is the intent of individuals to return to a certain place and their eventual inclination to revisit a destination more often.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, based on the broaden-and-build theory, 9,18 future research can measure how coaches' emotional responses influence athletes' behavioral outcomes to understand coach-athlete compatibility. Next, according to Cho and his colleagues, the concept of nostalgia, which is derived from positive experiences in the past and can be defined as the longing for the past, [91][92][93][94] is a significant antecedent of individuals' future behavior [95][96][97][98] and well-being. [99][100][101] Hence, this study suggests that future research develops a nostalgia scale for sport coaches by following Menor and Roth's 102 scale development procedure.…”
Section: Limitations and Future Researchmentioning
confidence: 99%